Francona [compact disc, unabridged] : the Red Sox years - Francona, Terry, 1959- (Macmillan Audio, 2013)
Terry Francona the legendary manager of the Boston Red Sox opens up for the first time about his eight years there. Those eight years were a wild ride, unforgettable ride, and now the fascinating full story can be told in a book that examines like no other the art of managing in today's game.